Review papersThe role of KIT gene mutations in pathogenesis of pediatric mastocytosis - Dawicka, Joanna; Lange, Magdalena; Wasąg, Bartosz; Nedoszytko, Bogusław; Wilkowska, Aleksandra; Nowicki, Roman (Dermatology Review/Przegląd Dermatologiczny, 2015)
Mastocytosis is characterized by excessive proliferation and accumulation of mast cells in skin and/or other organs. Two forms of the disease, cutaneous and systemic mastocytosis, differ significantly in symptomatology and clinical course. KIT mutations play an important role in the pathogenesis of the disease. The presence of p.D816V KIT mutation was detected in the vast majority of adults with systemic mastocytosis. The role of KIT mutations in childhood-onset mastocytosis remains a matter of discussion. More recent studies have shown that cutaneous mastocytosis, which is the most common clinical manifestation of the disease in children, has a genetic background. In contrast to adults, different types of KIT mutations have been described in pediatric and familial mastocytosis. The understanding of the molecular mechanisms in mastocytosis enables targeted therapy using tyrosine kinase inhibitors.